Business Management Literation And Legality E-Commerce In The Pandemic - Nurjanti Takarini; Anajeng Esri Edhi Mahanani; Eko Wahyudi (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
This article discusses the community service activities that have been carried out in the PKK RT / RW 005/005 Manukan Kulon group, Surabaya. This community service activity is held with the consideration that the author as an academic feels the need to participate in parsing the economic problems in society caused by the Covid-19 pandemic. The impact of the Covid-19 pandemic, which created many unemployment clusters due to layoffs from closed businesses, as well as macroeconomic impacts that affect the economic conditions of the Indonesian State, require the contribution of solutions from all parties, including academics who have the dharma of community service. Business management literacy andlegality are e-commerce implemented as a means of providing understanding to the community and building PKK groups that are legally aware and smart in managing their business by utilizing information technology media.